Variations in rates of severe perineal tears and episiotomies in 20 European countries: a study based on routine national data in Euro‐Peristat Project. (5th April 2016) - Blondel, Béatrice; Alexander, Sophie; Bjarnadóttir, Ragnheiður I.; Gissler, Mika; Langhoff‐Roos, Jens; Novak‐Antolič, Živa; Prunet, Caroline; Zhang, Wei‐Hong; Hindori‐Mohangoo, Ashna D.; Zeitlin, Jennifer; ,
Abstract: Introduction: Rates of severe perineal tears and episiotomies are indicators of obstetrical quality of care, but their use for international comparisons is complicated by difficulties with accurate ascertainment of tears and uncertainties regarding the optimal rate of episiotomies. We compared rates of severe perineal tears and episiotomies in European countries and analysed the association between these two indicators. Material and methods: We used aggregate data from national routine statistics available in the Euro‐Peristat project. We compared rates of severe (third‐ and fourth‐degree) tears and episiotomies in 2010 by mode of vaginal delivery ( n = 20 countries), and investigated time trends between 2004 and 2010 ( n = 9 countries). Statistical associations were assessed with Spearman's ranked correlations (rho). Results: In 2010 in all vaginal deliveries, rates of severe tears ranged from 0.1% in Romania to 4.9% in Iceland, and rates of episiotomies from 3.7% in Denmark to 75.0% in Cyprus. A negative correlation between the rates of episiotomies and severe tears was observed in all deliveries (rho = −0.66; p = 0.001), instrumental deliveries (rho = −0.67; p = 0.002) and non‐instrumental deliveries (rho = −0.72; p < 0.001). However there was no relation between time trends of these two indicators (rho = 0.43; p = 0.28). Conclusions: The large variations in severe tears and episiotomies and the negative association between these indicators in 2010 show the importance of improving the assessment and reporting of tears in each country, and evaluating the impact of low episiotomy rates on the perineum.